AUTONOMOUS AND BUSINESS PRACTICES IN NURSING - Joice Aparecida de Morais; Maria do Carmo Lourenço Haddad; Mariana Angela Rossaneis; Larissa Gutierrez de Carvalho da Silva (Universidade Federal do Paraná, 2013)
This descriptive study with a quantitative approach aimed to characterize the business practices in nursing in the state of Paraná. An intentional sample was undertaken by invitation to 11 nurses with businesses in the health area, the data collected via an online questionnaire. The results point to a young adult population; with a predominance of females and with varying professional experience. The interest in entrepreneurship arose from the search for professional satisfaction; business management was emphasized as the skill necessary to run a business. In relation to the easy aspects and difficulties for opening one's own business, support from other professionals and bureaucratic issues stand out; the participants showed themselves to be satisfied with their businesses. It is concluded that nursing has sought and explored a new market, promoting the profession as able to conduct its practice autonomously and innovatively.